Contribution of psychiatric diagnoses to extent of opioid prescription in the first year post‐head and neck cancer diagnosis: A longitudinal study. Issue 1 (5th November 2018) - Henry, Melissa; Alias, Ali; Frenkiel, Saul; Richardson, Keith; Hier, Michael; Zeitouni, Anthony; Kost, Karen; Mlynarek, Alex; Black, Martin; MacDonald, Christina; Chartier, Gabrielle; Rosberger, Zeev
Abstract: Purpose: The purpose of this study was to determine, within the first‐year post–head and neck cancer (HNC) diagnosis, the contribution of past and upon HNC psychiatric diagnoses (ie, substance use disorder, major depressive disorder, and anxiety disorder) to the extent (ie, cumulated dose) of opioid prescription. Methods: Prospective longitudinal study of 223 consecutive adults (on 313 approached; 72% participation) newly diagnosed (<2 weeks) with a first occurrence of primary HNC, including Structured Clinical Interviews for DSM‐IV disorders, validated psychometric measures, and medical chart reviews. Opioid doses were translated into standardized morphine milligram equivalents (MME) using CDC guidelines. A model of variables was tested using multiple linear regression. Results: Fifty‐five percent (123/223) of patients received opioids at some point during the first 12 months post–HNC diagnosis, 37.7% (84/223) upon HNC diagnosis (pre‐treatment), 40.8% (91/223) during treatments, and 31.4% (70/223) post‐treatment. The multiple linear regression indicated that an AD ( P = 0.04) upon HNC diagnosis in early stage contributes to cumulated MME dose in the first year post–HNC diagnosis. Conclusion: This study underlines how anxiety has important repercussions on the management of pain and illustrates the importance of screening for AD upon HNC diagnosis to allow for early prophylactic treatment and support.